Quản trị công, chi tiêu công và tăng trưởng kinh tế ở các quốc gia đang phát triển - Tran Trung, Kien; Su Dinh , Thanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
Whether any linkages exist among public expenditures, public governance, and economic growth is still a matter of debate. Using a panel covering 66 developing countries for the 1998–2016 period, this paper seeks to examine the role of public governance in the nexus between public expenditures and economic growth. By adopting GMM estimates, the empirical results indicate that public governance generally improves the positive effects of public expenditure components on growth. Interestingly, public governance enhances the growth effect of productive public expenditures. The difference in political institution, in addition, plays a major role in explaining the associations among public expenditures, public governance, and economic growth in developing countries.